(untitled) (IJM: Journal of Multidisiplinary, 2025)
Auditory hallucinations are sensory perceptions that occur in a person without appropriate stimulation. If this condition is not treated properly, it can have a negative impact on the patient's quality of life, including increasing the risk of violent behavior, social isolation, low self-esteem, and difficulty in self-care. This case study aims to explain comprehensive nursing care with a nursing process approach for hallucination patients at the Aceh Mental Hospital. The method used is a six day case study with the application of general therapy and the development of personal planning in one patient with auditory hallucinations. The results of this case study showed a decrease in the level of hallucinations from moderate (scale 16) to mild (scale 10) and an increase in patient knowledge and independence in overcoming problems. The conclusion of this case study is the application of general therapy and the development of personal planning appears to be effective in reducing the signs and symptoms of hallucinations. It is hoped that the development of personal planning can be applied in the healing program for hallucination patients at the Aceh Mental Hospital.